The IMPACT OF WAGE SCALE STRUCTURE AND WORK STATUS PROTECTION ON EMPLOYEE LOYALTY - Pertiwi, Dyah Nurul Bayu; Muzaroah, Siti; Sundari, Pipit (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2024)
The era of globalization with the elimination of trade barriers between countries has intensified business competition. One way to survive is to increase organizational productivity starting with improving human resource performance through salaries, wages, and performance-based rewards. This study aims to analyze the effect of implementing a wage scale structure and work status protection on employee loyalty at PT Apparel One Indonesia. This study involved 30 employees from the order management department as a population and sample. The variables studied were the Implementation of a Wage Scale Structure (X1), Work Status Protection (X2), and Employee Loyalty (Y). Data were collected through questionnaires and analyzed using validity, reliability, classical assumptions, and multiple linear regression analysis, t-test, F-test, and R² test. The results of this study confirm the importance of implementing a wage scale structure and work status protection as the main factors supporting increased employee loyalty. With a contribution of 43.1%, these two variables have a significant influence in building a positive relationship between the company and employees. This conclusion highlights that a fair and employee-oriented human resource management strategy not only improves individual performance but also creates long-term organizational stability. This research provides a strong basis for companies to continue to improve related policies and opens up opportunities for further studies on other variables that influence employee loyalty